2011
DOI: 10.1097/00004872-201106001-01680
|View full text |Cite
|
Sign up to set email alerts
|

Eprosartan-Based Hypertension Therapy, Systolic Arterial Blood Pressure and Cognitive Function: Analysis of Middle East Data From the Oscar Study

Abstract: Background: Studies have indicated a relationship between hypertension and cognitive function. The possible effect of antihypertensive therapy on cognitive disorders is therefore a matter of interest. Materials and methods:The Observational Study on Cognitive function And SBP Reduction (OSCAR) was an open-label, multinational trial designed to evaluate the impact of eprosartanbased antihypertensive therapy on cognitive function in patients with essential hypertension. Eprosartan 600 mg/day for 6 months (with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The initial results showed that MMSE scores were significantly increased compared to baseline after Eprosartan treatment (+ 0.8 points; P < 0.0001) [47]. In a subsequent study, [48] it was shown that, in addition to lowering BP, Eprosartan treatment reduced pulse pressure, suggesting that AT1 receptor antagonists may reduce arterial stiffness and contribute to cognitive improvement.…”
Section: Angiotensin II Receptor Blockers (Arbs)mentioning
confidence: 97%
“…The initial results showed that MMSE scores were significantly increased compared to baseline after Eprosartan treatment (+ 0.8 points; P < 0.0001) [47]. In a subsequent study, [48] it was shown that, in addition to lowering BP, Eprosartan treatment reduced pulse pressure, suggesting that AT1 receptor antagonists may reduce arterial stiffness and contribute to cognitive improvement.…”
Section: Angiotensin II Receptor Blockers (Arbs)mentioning
confidence: 97%
“…Furthermore, increased arterial stiffness is a significant predictor of subsequent cognitive decline [63]. Conversely, intervention studies have shown that drugs that can lower arterial stiffness have positive effects on cognitive function [64]. Neuroimaging studies have shown associations between aortic stiffness and measures of brain integrity.…”
Section: Klohsmentioning
confidence: 99%
“…(assessed with the MMSE) with respect to baseline measures (Radaideh et al 2011). The protective effect of antihypertensives in preventing cognitive decline remains a matter of debate; for a recent discussion on this topic the reader is referred to a recent review .…”
Section: Blood Pressure-lowering Drugsmentioning
confidence: 99%